Dumbbell Shaped Microstrip Broadband Antenna - Sudeep Baudha; Harshit Garg; Manish Varun Yadav (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract In this article, a dumbbell shaped microstrip broadband microstrip antenna with partial ground plane is presented, The overall dimension of the proposed antenna is 20 × 15 × 1.5 mm3 and is fabricated on FR4 substrate which has electrical permittivity of 4.3 and loss tangent of 0.025. FR4 is a low cost and easily available. The thickness of the substrate is 1.5 mm. The impedance bandwidth of the proposed antenna is 151.11 % (3.48 GHz to 25 GHz). The peak gain and radiation efficiency of the proposed antenna are 4.5 dB and 68 % respectively in the operating frequency band. Due to introduction of rings on the edges of the octagon and cutting of circular slots with the rectangular slits in the ground plane the antenna starts resonating from 3.48 GHz to 25 GHz. Simulated results are in good agreement with the measured results. The proposed antenna covers partial frequency range for ultra-wide band applications, 3.5/5.5 GHz WiMAX band, 5.2/5.8 GHz WLAN band, 8/12 GHz X-band, 12/18 GHz Ku -band. It can be used in space and satellite communications etc. Curves of radiation pattern and S-parameter of both simulated and measured results are shown. The impedance curves, surface current, radiation efficiency, simulated return losses, gain, and radiation patterns of the proposed antenna are described in the paper.